IMPLEMENTASI PROGRAM HAFALAN SURAT PENDEK DALAM PEMBENTUKAN KARAKTER ANAK DIDIK DI RA AL-IZZAH KOTA SERANG BANTEN - Khosiah, Siti; Utami, Nurul Putri; Amalia, Jihan (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2025)
Education is something that is certain and occurs naturally. RA Al-Izzah formal education is one of the education owned by the Al-Izzah foundation in the city of Serang, education which has an excellent program, namely memorization. The memorization that is carried out is not only hadith, but there is also memorization of short letters up to daily prayers, this is based on the goals and vision and mission of the Al Izzah Foundation, especially RA Al-Izzah who wants to have an intelligent, independent and intelligent Qur'an generation. Have noble character. In the memorization process, RA Al-Izzah also has a memorization method, memorization time, and assessment time which are arranged systematically so that children are able to understand, capture and memorize according to their wishes and learning objectives so that students can achieve these learning objectives. In this research, the aim of the author is to find out the systematic implementation of memorization implemented by RA Al-Izzah, Serang City, and in carrying out the research, interview techniques were used by digging up data from existing teaching staff and then processing it into written work using qualitative methods